The role of corporate social responsibility in organizational reputation: A systematic review and bibliometric analysis - Herrera, Cesar Augusto Montoya; Valderrama, Diego Alejandro Villa; Lievano, Jhony Alexander Barrera; Virgüez, Jesús Enrique Beltrán; Ramirez, Sandra Miyey Parra (Edelweiss Applied Science and Technology, 2025)
This research addresses issues related to the adoption of Corporate Social Responsibility (CSR) practices by companies and their impact on corporate reputation. It is based on the premise that poor practices associated with CSR implementation can damage a company’s corporate image and its market position. The objective was to determine the impact of corporate social responsibility on organizational reputation in light of existing scientific literature. To achieve this, a systematic literature review was conducted following the PRISMA protocol and the recommendations proposed by Petticrew and Roberts (and their adaptation by Gast et al. for application in social sciences). The study used the Scopus database, from which 176 initial documents were identified, and 96 were selected according to inclusion and exclusion criteria. The results show that when companies implement CSR authentically, they enhance public image perception, increase consumer trust, strengthen human talent management, and gain competitive advantages aligned with sustainability. However, strategies such as greenwashing negatively affect organizational credibility. In conclusion, CSR should be integrated into organizational culture and strategy to become a fundamental element of both reputation and corporate strategy.